Upper Respiratory Tract Infections And Their Association With Knowledge, Attitude And Practice Among Malaysian Hajj Pilgrimsof 2007 A.d (1428 H) - Mansoor, Sarab Malik (2009)
Setiap tahun lebih dari dua juta Muslim daripada lebih 140 negara menunaikan ibadat haji di Mekah dan Madinah.